“Without love you can not develop a good work”: analysis of social representation of teachers inclusion on school - Albuquerque, Ednéia Rodrigues (2009)
The educational legislation, and the National Policy on Education in Brazil highlight the Special Education as a means of education, offered, preferably in the regular school network, whose guiding principle is the inclusion. This article presents the results of a study of social representations to include school teachers between the public network developed in the Graduate Program in Education at the Federal University of Pernambuco - UFPE. Participants in the survey are 43 teachers of students with disabilities in the municipal network of Jaboatao of Exmouth-EP. Data were collected through the free association of words and the results indicate that the inclusion in school social representation of teachers is an act of love. The character of the emotional evocations excels is in the social representations of students with disabilities affecting the meaning of inclusion as a right of a student with disabilities. Thus, the Special Education, despite its merits and achievements, such as social right constitutionally guaranteed to persons with disabilities continues to be denied.